Selective punitiveness among social work students: A longitudinal study - Hanslmaier, Michael (Probation journal, 2025)
This article presents the primary results of a longitudinal study on attitudes toward punishment, among social work students in Germany. This is particularly relevant because social workers, especially in the field of criminal justice, are part of the state control bodies required to set boundaries and decide for or against certain sanctions. The results show that punitive attitudes are not uncommon among first-year social work students but decrease during the course of their study, especially in students majoring in the field of criminal justice. Simultaneously, “selective punitiveness” was evident.